Pengaruh Penggunaan Flash Card Dan Permainan PlayDough Terhadap Pengembangan Karakter Anak Usia Dini (Effects of Using Flash Cards and Playdough Games on Early Childhood Character Development) - Nur Hidayati; Rudy Sumiharsono; Eges Triwahyuni (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The aim of the research was to find out whether using flashcard media and playdough games could develop character in early childhood group B TK AL Bukhori Kaligondo. Variable X1 ( flashcard) indicators 1) Recognize word cards, 2) Recognize letter cards, 3) Recognize picture cards. Variable X2 (Playdough Game) indicator 1) Making Playdough shapes, 2) Playdough Coloring, 3) Forming patterns. Variable Y (Character Development). This research uses a causal quantitative research method. According to Sugiyono (2017), a causal quantitative approach is an approach in research that looks for relationships between one variable and other variables that have causation. This research tests the established hypotheses and to look for the influence between the independent variable and the dependent variable. Data collection: 1). observation, 2). interview, 3). document. Data analysis 1) instrument test, 2) classic assumption test, 3) hypothesis test. The results of t-test the effect of Flashcard Media on children's character development (11.829> 2.03452), the effect of Playdough Games on children's character development (6.667> 2.03452), the f test of the effect of Flashcard Media and Playdough games on children's character development. So it can be concluded that Flashcards and Playdough games have an effect on children's Character Development and H0 is rejected.